The poetics of decadence in S. George’s «Algabal» cycle - Kurylau, Yury G. (Journal of the Belarusian State University. Philology, 2024)
Based on the material of the cycle of poems «Algabal» by S. George, an attempt to reveal the features of the early lyric poetry of the German poet is made. It is shown that the decadent view on the substantive and formal levels is determining for the cycle. The main themes and leitmotifs illustrated in the cycle are the opposition of the natural and the illusory, the reduction of life to the phenomenon of art, the unity of beauty and death. In the studied poems various non-realistic styles of the turn of the 19th–20th centuries are revealed: impressionism serves to symbolise emotions through the concentration of colour and the emphatically fragmentary technique of developing a poetic statement; aestheticism is manifested in the absolutisation of the role of art, the glorification of elitism and exclusivity, the escapist tendency and the creation of a special concept of the hero, for whom beauty is the meaning of life; the neo-romantic craving for the irrational, fantastic and exotic elements crystallises in the image of an exceptional personality; symbolist poetics takes shape, hinting at a transcendent reality. The meaning-forming role of rhythmic and phonetic features and their connection with the lexico-semantic level, as well as the special function of rhyme, which clarifies hidden verbal relations, are established.